PERAN GURU DALAM PEMBELAJARAN BERDIFERENSIASI UNTUK MENENTUKAN STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MTs JAMSAREN SURAKARTA - Amanah Qurata A'yun; Sukari Sukari (STKIP Pesisir Selatan, 2026)
This study analyzes teachers’ roles in differentiated instruction, the Islamic Religious Education learning strategies employed, and the barriers to their implementation at MTs Jamsaren Surakarta during the 2025/2026 academic year. The study used a descriptive qualitative approach with a case study design. The informants included the principal, vice principal for curriculum affairs, Islamic Religious Education teachers, and students. Data were collected through interviews, participant observation, and documentation. The data were analyzed interactively through data collection, condensation, display, and conclusion drawing and verification. Source, technique, and time triangulation strengthened the credibility of the findings. The results show that teachers served as instructional designers, facilitators, mentors, motivators, classroom managers, and evaluators. Teachers conducted diagnostic assessments to map students’ readiness, interests, and learning profiles, and then differentiated content, process, product, and learning environment. The strategies included interactive lectures, questioning, discussion, group work, presentations, peer tutoring, problem-based learning, practice, instructional videos, and tiered assignments. These approaches increased participation and helped students understand Islamic Religious Education materials. The main barriers involved wide differences in student ability, limited instructional time, large classes, uneven teacher understanding, low learning motivation, and limited media.